Pendekatan Saintifik Dalam Prinsip Kerjasama Pada Pembelajaran Bahasa Indonesia di Sekolah - Sakdiah, Lailatul (khatulistiwa, 2020)
In essence, communication is the interaction of establishing social relations which are carried out by using expressions of politeness and implicit expressions. This strategy is carried out by the speaker and the interlocutor so that the message is conveyed properly. Thus the communication process is established perfectly. In classroom learning with a scientific approach, students are required to actively interact, especially during discussions so that activities with the principle of cooperation will emerge and of course, the principles of politeness will emerge. In interacting, commitment is needed to work together in order to create effectiveness in achieving learning objectives. Of course, this cooperation is based on the use of speech with the politeness principle with the scale proposed by Geoffrey N. Leech, Brown and Levinson, and Robin Lakoff.